Effect of different fiber sources and tert-butylhydroquinone on the quality characteristics of chicken harrisa, a meat based product. Issue 6 (9th November 2015) - Kumar, Lokesh; Bhat, Z. F.; Kumar, Sunil
Abstract : Purpose: – This paper aims to evaluate the effect of different fiber sources and tert-butylhydroquinone (TBHQ) on the quality characteristics of chicken harrisa . Design/methodology/approach: – An attempt was made to develop fiber-enriched chicken harrisa, a meat-based product, by incorporating optimum level of different fiber sources, viz., oat bran (10 per cent) or wheat bran (10 per cent) or barley bran (5 per cent). The products developed with optimized level of fiber were further treated with TBHQ (200 ppm) and were aerobically packaged in low-density polyethylene pouches along with control and assessed for various storage quality parameters under refrigerated (4 ± 1°C) conditions. The products were evaluated for various physicochemical, microbiological and sensory parameters at regular intervals of 0, 7, 14 and 21 days. Findings: – A significant ( p < 0.05) increase was observed in the fiber content of the products prepared with oat bran (10 per cent) or wheat bran (10 per cent) or barley bran (5 per cent). TBHQ showed a significant ( p < 0.05) effect on the lipid oxidative stability, as the treated products exhibited significantly ( p < 0.05) lower thiobarbituric acid-reactive substance (mg malonaldehyde/kg) values for the entire period of storage. No significant ( p > 0.05) effect was observed on the microbiological characteristics of the products. Sensory parameters showed significant ( p < 0.05) decreasing trend for control as well as TBHQ-treated products throughout the period of storage; however, significantly ( p < 0.05) higher scores were observed for treated products in comparison to control. Originality/value: – Fiber-enriched chicken harrisa was developed by incorporating oat bran (10 per cent) or wheat bran (10 per cent) or barley bran (5 per cent) in the formulation. TBHQ successfully improved the lipid oxidative stability and storage quality of fiber-enriched chicken harrisa during refrigerated (4 ± 1°C) storage and may be commercially exploited to improve the storage quality of the product.